ANALISIS KOMPARATIF SERVICE EXCELLENT ANTARA BPR ARTHA JAYA MANDIRI DENGAN BPRS AL-MADINAH DI TASIKMALAYA - Joni Joni (Jurusan Akuntansi Politeknik Negeri Bandung, 2018)
This study aims to find out service excellent at BPR Artha Jaya Mandiri, service excellent at BPRS Al-Madinah, and the differences. The sample used is the number of customers of BPR Artha Jaya Mandiri 100 people, and 100 customers of BPRS Al-Madinah. The analysis technique uses the t test and 2 independent samples. The results of service excellent research at BPR Artha Jaya Mandiri amounted to 60.88, and service excellent at BPRS Al-Madinah was 60.06. Based on the results of testing the hypothesis it is proven that t count <t table at the 0.05 level of significance, and the results compare the mean between the average service excellent scores at BPR Artha Jaya Mandiri and BPRS Al-Madinah only difference of 0.82. So there is no significant difference between the excellent service of BPR Artha Jaya Mandiri and BPRS Almadinah. Keywords: Service Excellent, BPR, BPR Syariah.